FUNGSI BAHASA (DALAM LEGENDA RAKYAT KALIMANTAN TENGAH) - Maria Arina Luardini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract From the perspective of social semiotics, language has two dimensions: expression and content. The expression will not have a content (meaning) when it is not in used (Halliday dan Hasan, 1985: 17). Language function which is expressed in the legends belonged to the Dayak Ngaju community (LDN) in Central Kalimantan is suitable to the theory of language function proposed by Halliday and Hasan (1985: 17) rather than other theories. The language function within LDN consists of informative function, interactive, and imaginative.